Impact of liquidity management in financial performance on commercial banks in embu kenya - KYAMBI, JULIUS (UoEm, 2024)
Commercial banks are useful organizations in providing financial services to people, governments, and business enterprises. Commercial banks have been useful to the Kenyan economy by providing huge amounts of money through tax. it has been a threat in commercial banks due to their incapacity to maintain a required and sufficient amount of liquid. The overall performances of commercial banks have therefore been slowed. The global financial crisis of the year 2007-2008 was a depiction of the importance of liquidity. The crisis witnessed in 2007-2008 was a result of the failure to balance cash inflows and cash outflows. They're due to undermining liquid analysis and forecast has resulted in a very high level of cash imbalance. Therefore this study seeks to investigate the effect of liquidity risks on commercial banks in Kenya. The study will be guided by the following objectives for study as follows: impact of bank sizes, the quality level of assets, Efficiency, and effective adequacy on the financial performance of commercial banks in Kenya. The effect of money supply on the relationship between liquidity risks and the financial performance of commercial banks will also be determined. The causal research design will be adopted in this study aiming at studying 7 commercial banks located in Embu municipality. Secondary data and primary data were used in the research study. The secondary data will be extracted from financial books from KCB at Embu town data analysis will be taken through the use of questionnaires. The study will offer recommendations to commercial banks on how to diversify their product portfolio to expand their income revenue.